Structural characterization and crystal packing of the isoquinoline derivative - Vrabel, Viktor; Svorc, Lubomir; Sivy, Julius; Marchalin, Stefan; Safar, Peter (European Journal of Chemistry, 2018)
We report the crystal and molecular structure of a new isoquinoline-derivative, namely methyl O-[(11R, 11aS)-4-oxo-1, 3, 4, 6, 11, 11a-hexahydro-2H-pyrido[1, 2-b]isoquinolin-11-yl]carbonodithioate (I), C15H17NO2S2, which crystallizes in the non-centrosymmetric space group P212121 and its absolute structure was confirmed by anomalous dispersion effects in diffraction measurements on the crystals. Two central six-membered heterocyclic rings adopt a distorted half-chair conformation. The molecules are linked by a combination of weak C—H∙∙∙O, C—H∙∙∙S, C—H∙∙∙p inter- and intra-molecular interactions resulting in a three-dimensional network in the crystal structure. Crystal Data for C15H17NO2S2 (M =307.41 g/mol): orthorhombic, space group P212121 (no. 19), a = 5.2804(5) Å, b = 8.1347(17) Å, c = 35.015(4) Å, V = 1504.1(4) Å3, Z = 4, T = 298(2) K, μ(MoKα) = 0.354 mm-1, Dcalc =1.358 g/cm3, 20270 reflections measured (5.522° ≤ 2Θ ≤ 50.69°), 2757 unique (Rint = 0.0346, Rsigma = 0.0203) which were used in all calculations. The final R1 was 0.0389 (I > 2σ(I)) and wR2 was 0.0965 (all data).